Design of Hybrid Fuels Using a Modeling Study of the Miscibility of Ethanol–Biodiesel–Hydrocarbon Systems - Pina-Martinez, Andrés; Juntarachat, Niramol; Privat, Romain; Coniglio, Lucie; Molière, Michel; Jaubert, Jean-Noël (International journal of thermophysics, 2016)
Recently, the concept of diesel–ethanol blends has emerged as an alternative to regular diesel oils. However, these blends present serious stability limitations entailed by the contrasted physicochemical properties of hydrated ethanol and diesel oil. Biodiesel is often used as a third solvent since it behaves successfully as a surface-active agent to stabilize ethanol/diesel fuel blends. In this paper, a flash algorithm, employing the UNIFAC-Dortmund g E -model for calculating the activity coefficients, has been used to evaluate the Minimal Miscibility Temperature (MMT) of alcohol–biodiesel–hydrocarbon systems. The simulation work was focused on the influence of various parameters such as the paraffinic/aromatic/naphthenic character of the hydrocarbon fraction, the hydration level of the alcohol, the size of the alcohol molecule, and the composition of the added biodiesel. The results show that biodiesel enhances ethanol/hydrocarbon miscibility whichever the nature of the fossil fractions. They also highlight the importance of the aromatic content of the fuel in the miscibility of the alcohol/hydrocarbon blends. The chain moiety of the alcohol as well as its hydration degree were found relevant for the fuel blends stability. Conversely, while increasing biodiesel concentration leads to significant decreases of the MMT, the influence of the biodiesel chemical structure remains practically insignificant.